Awareness, Knowledge, and Attitudes Toward Screening and Treatment of Masked Hypertension in Primary Care. (19th July 2021) - Boyd, Rebekah; Carter, Eileen; Moise, Nathalie; Alcántara, Carmela; Valadares, Thais; Anstey, D Edmund; Kronish, Ian M
Abstract: Background: Hypertension guidelines recommend screening and treatment for masked hypertension (MHT). Yet, few primary care providers (PCPs) screen for MHT, and little is known about PCP awareness, knowledge, and attitudes toward MHT. Methods: Three focus groups involving 30 PCPs from 3 medical centers in New York were conducted. Focus group transcripts were analyzed using thematic content analysis. Results: Awareness of MHT varied, and only 2 providers had diagnosed MHT. There was also low knowledge about the prevalence and impact of MHT. While some PCPs were receptive to MHT screening after learning about its significance, others viewed the current evidence as insufficient to change practice. Providers were discomforted by labeling patients with nonelevated office blood pressure (BP) as hypertensive and reluctant to add another screening test to their workload without stronger evidence. There was distrust in the accuracy of home BP monitoring to screen for MHT. There was more confidence in ambulatory BP monitoring (ABPM) for MHT screening, but ABPM was viewed as largely inaccessible. There was broad agreement with lifestyle changes for MHT. There were concerns that antihypertensive medication lacked evidence from randomized trials and could induce harmful side effects. Conclusions: Limited PCP knowledge about MHT, concerns about the accuracy and accessibility of screening tests, overloaded PCPs, and insufficient evidence were major barriers to screening and treatment for MHT. Prior to broad uptake by PCPs, randomized trials demonstrating the net benefits of MHT screening and treatment may be needed, along with increased dissemination of knowledge about MHT and improved access to ABPM.